Relationship Between Service Quality, Service Satisfaction, and Outpatient Loyalty Following Electronic Medical Record Implementation at Dr. R. Soetijono Regional Hospital, Blora - Gabriella Alicea; Yura Witsqa Firmansyah; Afif Kurniawan (Asosiasi Dosen Muda Indonesia, 2026)
The implementation of Electronic Medical Records (EMR) is expected to improve healthcare service quality and strengthen patient loyalty by enhancing service quality, and service satisfaction. This study aimed to analyze the relationship between service quality, and service satisfaction with outpatient loyalty after EMR implementation at RSUD dr. R. Soetijono Blora. Method: This study employed a quantitative cross-sectional design involving 100 outpatient respondents selected using accidental sampling. Data were collected through validated and reliable questionnaires and analyzed using univariate analysis and the Spearman Rank test with a significance level of 0.05. Findings: The results showed that most respondents perceived service quality (95%), and service satisfaction (76%) as being at a moderate level, while patient loyalty was categorized as high (100%). Statistical analysis indicated that service quality, hospital image, and service satisfaction were not significantly associated with patient loyalty (p>0.05). Implications: These findings suggest that maintaining patient loyalty after EMR implementation requires attention to additional factors beyond service quality, and service satisfaction, providing valuable input for hospital management in evaluating digital health service strategies. Originality: This study offers empirical evidence regarding outpatient loyalty following EMR implementation in a regional public hospital and demonstrates that high patient loyalty may persist despite the absence of significant relationships with the examined service-related factors.